Development of an Intelligent Human Following Robot as an Automated Shopping Assistant - Al Fathir Zaki Mustofa (International Journal of Electrical and Intelligent Engineering, 2025)
The human following robot technology presented in this research offers an innovative solution for modern shopping needs. Designed to automatically follow human movement within a distance of 1–15 cm, the robot stops when the distance exceeds this range, ensuring safe operation. As shopping activities in the modern era increasingly demand efficiency and convenience, this robot has strong potential to function as an environmentally friendly personal assistant, helping users carry groceries in supermarkets and malls without relying on plastic bags. The system is built using an Arduino Uno as the central controller, supported by a motor driver, DC motors, wheels, a servo motor, an ultrasonic sensor, and infrared sensors. The ultrasonic sensor measures human distance, while infrared sensors detect the position of objects on the right and left sides. Sensor data is processed to adjust motor direction and speed, enabling the robot to follow users safely. The development of this robot is expected to enhance shopping experiences and support broader applications of robotics in daily life.